PERAN ORANG TUA DALAM PENDIDIKAN ISLAM BERDASARKAN Q.S. AT-TAHRIM AYAT 6 - Al Ayyubi, Ibnu Imam; Abdullah, Dindin Sofyan; Nurfajriyah, Dewi Syifa; Yasmin, Sabrina; Hayati, Ai Faridatul (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This research aims to integrate the values ??contained in the Al-Quran, especially in Q.S at-Tahrim verse 6 regarding the role of parents in educating children's behavior and character which is inherent in Islamic religious education. The method used in this research is qualitative. Data collection techniques carried out by researchers used observation and interviews. Based on qualitative research methods, all facts, both written and verbal, from primary and secondary data sources are described as they are and then studied to be reduced as concisely as possible to answer the problem. Data analysis techniques in this research include data collection, data reduction, data presentation, and conclusion. In this research, it can be concluded that the role of parents in Islamic education based on Q.S. at-Tahrim verse 6 is very relevant and can be actualized in the contemporary era where Westernization is increasingly being embraced by children from an early age. This is relevant to what is contained in the Al-Quran in Surah at-Tahrim verse 6 where there is a command to always fear Allah SWT and preach, advice to protect oneself and one's family from the torment of hell, the importance of Islamic education from childhood to understand the religion that is respected. by Allah SWT, and faith in angels which is one part of the pillars of faith.